2003
DOI: 10.1128/jvi.77.21.11708-11717.2003
|View full text |Cite
|
Sign up to set email alerts
|

Severe CD4+T-Cell Depletion in Gut Lymphoid Tissue during Primary Human Immunodeficiency Virus Type 1 Infection and Substantial Delay in Restoration following Highly Active Antiretroviral Therapy

Abstract: Gut-associated lymphoid tissue (GALT) harbors the majority of T lymphocytes in the body

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

35
640
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 771 publications
(684 citation statements)
references
References 23 publications
35
640
1
8
Order By: Relevance
“…However, Li et al, using in situ hybridization to detect SIV RNA, concluded that only ϳ7% of mucosal CD4 ϩ cells were productively infected by SIV during acute infection, thus supporting the hypothesis that apoptosis-mediated death is a pivotal mechanism sustaining mucosal T-lymphocyte depletion (77). Similar data have also been obtained by serial gastrointestinal tract sampling in HIV-infected individuals during early stages of infection, although the depletion of intestinal CD4 ϩ CCR5 ϩ T cells appeared to be somewhat less dramatic than in the SIVmac infection model (34,35,71). Following the acute phase of infection, CD4 ϩ T-cell depletion in the intestinal mucosa has been shown to continue throughout chronic disease to a much greater extent than in the peripheral blood and lymph nodes.…”
Section: Pathogenesis Of Hiv/siv-associated Microbial Translocationsupporting
confidence: 70%
See 3 more Smart Citations
“…However, Li et al, using in situ hybridization to detect SIV RNA, concluded that only ϳ7% of mucosal CD4 ϩ cells were productively infected by SIV during acute infection, thus supporting the hypothesis that apoptosis-mediated death is a pivotal mechanism sustaining mucosal T-lymphocyte depletion (77). Similar data have also been obtained by serial gastrointestinal tract sampling in HIV-infected individuals during early stages of infection, although the depletion of intestinal CD4 ϩ CCR5 ϩ T cells appeared to be somewhat less dramatic than in the SIVmac infection model (34,35,71). Following the acute phase of infection, CD4 ϩ T-cell depletion in the intestinal mucosa has been shown to continue throughout chronic disease to a much greater extent than in the peripheral blood and lymph nodes.…”
Section: Pathogenesis Of Hiv/siv-associated Microbial Translocationsupporting
confidence: 70%
“…Such severe CD4 ϩ T-cell impairment has been shown to preferentially involve gut-residing memory-activated CD4 ϩ CCR5 ϩ T cells, reflecting the well-known prevalence of CCR5-tropic viruses in the early phases of infection. Almost concomitantly, Veazey et al and Kewenig et al showed that more than 70% of intestinal CD4 ϩ cells were depleted as early as 21 days post-SIVmac239 infection (72,73), and several subsequent studies then confirmed these findings and shed further light onto the mechanistic pathways underlying CD4 ϩ T-cell depletion (34,(74)(75)(76). Among those studies, Mattapallil et al were able to demonstrate the presence of SIV DNA in up to 60% of intestinal CD4 ϩ T cells as early as 10 days after experimental SIVmac251 infection, therefore emphasizing the role of direct virus-mediated killing of CD4 ϩ T cells as a mechanism causing the observed depletion (70).…”
Section: Pathogenesis Of Hiv/siv-associated Microbial Translocationsupporting
confidence: 48%
See 2 more Smart Citations
“…During the early expansion phase, massive numbers of CCR5 ϩ CD4 ϩ memory T cells in the gut mucosa become infected and disappear (38,55,62,93), and such a severe depletion of target cells is expected to slow down viral replication (75). Despite equal initial replication rates, the peak viral loads that are obtained in vaccinated monkeys can be 10-fold lower than those in naive monkeys (12,21,22,32,86).…”
mentioning
confidence: 96%